Hubungan Pola Pendampingan Orang Tua dengan Kebiasaan Screen Time pada Anak Paud Usia Pra Sekolah (3-6 Tahun) : A Systematic Literature Review - Sucita, Sucita; Novianti, Rima; Permana, Iwan (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
The rapid development of digital technology has increased screen time exposure among early childhood, particularly in the preschool age group (3–6 years), which is a critical phase for cognitive, language, and emotional development. The high duration of device usage exceeding the recommendations of the World Health Organization (WHO) indicates that children’s screen time habits are closely linked to the family environment, especially parental mediation patterns.This study aims to comprehensively analyze the relationship between parental mediation and screen time habits in preschool-aged children, as well as to identify the most effective mediation strategies for controlling digital media use. The study employs a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach.Data sources were obtained from several international databases, including Scopus, ScienceDirect, PubMed, Web of Science, Cochrane Library, and Google Scholar, covering publications from 2010 to 2026. The selected articles met inclusion criteria in the form of empirical studies discussing parenting patterns or parental mediation and screen time in preschool children. The data were analyzed narratively to identify relationship patterns and determinant factors influencing children’s screen use behavior.The findings indicate a significant relationship between parental mediation and both the duration and quality of children’s screen time. Restrictive mediation has proven to be the most effective in controlling screen time duration, while active mediation plays an important role in improving the quality of children’s digital experiences. In contrast, weak parental mediation, technoference, and the use of devices as a digital pacifier contribute to increased and uncontrolled screen time. In addition, parental modeling behavior is a key predictor in shaping children’s digital habits.In conclusion, the effective management of screen time in preschool-aged children strongly depends on the quality of parental mediation, including restriction, active interaction, and behavioral consistency. Therefore, balanced parenting strategies are needed through the implementation of a family media plan, enhancement of parental digital literacy, and the provision of non-digital alternative activities to optimally support children’s development in the digital era.